Hemodynamic Effects of Vecuronium at Time of Induction - H. Alkhashab, Radhwan; A. Hussein, Saad; H. Ismael, Intesar (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Objective: The aim of the study to evaluate the influence of vecuronium on heart rate, systolic & diastolic arterial blood pressure (hemodynamic stress response) during nitrous oxide – halothane anesthesia.A double-blind study was done in Aljamhori teaching hospital, Mosul city, Iraq from (February 2011 – May2013); All the patients were in the age of 16-47 years, and ASA1. In this study 60 patients males & females prepared for elective surgery; Vecuronium was administered to 30 patients named (Group A) & normal saline was administered to another 30 patients (Group B); Heart rate & arterial blood pressure were monitored immediately before induction, at time of induction & (0, 3, 4, 5) minutes after induction of anesthesia. There were no significant differences in sex, weight & age of patients also there was no significant differences statistically between the two groups (P > 0.05) in heart rate & arterial blood pressure in pre induction, after induction & maintenance of anesthesia. In conclusion; Vecuronium had no effect on hemodynamic stress response during general anesthesia.